ANALISIS KELAYAKAN FINANSIAL PENGEMBANGAN USAHATANI LABU MADU DI KABUPATEN PANDEGLANG PROVINSI BANTEN - Khaerul Saleh (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2020)
Besides having a high economic value, Pumpkin honey also has good nutritional content, technically honey pumpkin cultivation is no different from other plants, but in pumpkin, honey cultivation requires a higher investment, especially at variable costs, this study was conducted in Pandeglang district, in general, it is suitable for pumpkin honey cultivation. The objectives of this study include to: (1) Financial feasibility of pumpkin honey farming. (2) The rate of sensitivity (sensitivity) to the decline in selling prices, increase in production costs and decrease in the amount of production (3) The feasibility of the aspects of cultivation, social environment, economics and marketing of Pumpkin Honey. tabulation and computational methods to facilitate analysis. Data analysis uses quantitative analysis and qualitative descriptive analysis. Quantitative analysis analyzes financial feasibility (B/C Ratio, NPV, IRR and PBP) and sensitivity analysis using applicable interest rates, qualitative descriptive analysis is used to determine the feasibility of cultivation, social environmental, economic and marketing aspects. The results showed that (1) Honey Pumpkin Cultivation in Cipeucang and Cimanuk Subdistricts of Pandeglang Regency was feasible to be cultivated with Gross B/C Ratio, Net B/C Ratio, NPV.IRR and Payback Period (PBP) feasible. (2) The possibility of a decrease in production, a decrease in output prices, and an increase in production costs, according to investment criteria and in a proper condition, and have a good level of sensitivity. (3) The technical aspects of cultivation from climate and rainfall following the Pumpkin Honey plant, the social and environmental aspects are feasible, the marketing aspects are feasible and very promising.